Anti-hepatocellular carcinoma activity and mechanism of chemopreventive compounds: ursolic acid derivatives. (1st December 2016) - Huang, Qiuxia; Chen, Hongfei; Ren, Yuyan; Wang, Zhe; Zeng, Peiyu; Li, Xuan; Wang, Juan; Zheng, Xing
Abstract: Context: Hepatocellular carcinoma (HCC) is a common cancer around the world, with high mortality rate. Currently, there is no effective drug for the therapy of HCC. Ursolic acid (UA) is a natural product which exists in various medicinal herbs and fruits, exhibiting multiple biological effects such as its outstanding anticancer and hepatoprotective activity, which has drawn many pharmacists' attention. Objective: This paper summarizes the current status of the hepatoprotective activity of UA analogues and explains the related mechanism, providing a clear direction for the development of novel anti-HCC drugs. Methods: All of the data resources were derived from PubMed. By comparing the IC50 values and analyzing the structure–activity relationships, we listed compounds with good pharmacological activity from the relevant literature, and summarized their anti-HCC mechanism. Results: From the database, 58 new UA derivatives possessing wonderful anticancer and hepatoprotective effects were listed, and the relevant anti-HCC mechanism were discussed. Conclusion: UA's anti-HCC effect is the result of combined action of many mechanisms. These 58 new UA derivatives, particularly compounds45 and53, can be used as potential drugs for the treatment of liver cancer.